Dreams and Dust - Marquis, Don, 1878-1937 (Salt Lake City, UT : Project Gutenberg, 1996)
"Dreams and Dust" by Don Marquis is a collection of poems written during the early 20th century. The work reflects on themes of existence, the human condition, and the intersection of dreams and reality, allowing readers a glimpse into the profound emotional and philosophical struggles inherent to life. Marquis's verses explore various facets of humanity, woven through his unique lyrical style that captures both the beauty and sorrow of human experience. The beginning of "Dreams and Dust" sets a tone of introspection and hope, with the proem establishing a willingness to embrace life despite its challenges. The early poems invite readers to celebrate each new day, suggest a deep connection to nature, and reflect on the weight of past mistakes and regrets. As characters navigate through the themes of love, loss, and aspiration, Marquis illustrates a vivid landscape of emotions, giving voice to the universal hope for renewal and understanding amidst the complexities of existence. This initial exploration hints at the rich tapestry of ideas and feelings that will unfold throughout the collection. (This is an automatically generated summary.)
Release date is 1996-03-01
Produced by Judith Boss
Keywords: American poetry